Relationship between Physical Activity of Pregnant Women in the Third Trimester of Pregnancy with Preterm Birth Using Kaiser Physical Activity Survey (KPAS) Questionnaire: Hubungan antara Aktivitas Fisik Perempuan Hamil pada Trimester Ketiga Kehamilan dengan Persalinan Prematur Menggunakan Kuesioner Kaiser Physical Activity Survey (KPAS) - JM Seno Adjie; AA Rai D Maharani (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective: To examine the relationship between the intensity of physical activity of pregnant women with preterm birth and to know the relationship between types of physical activity of pregnant women with preterm birth. Method: This research was a case control study that was conducted at Dr. Cipto Magunkusumo Hospital and Karawang Hospital in January 2017 to June 2017 with KPAS questionnaire which was divided into two groups, preterm birth and term birth. The sample size was 127 subjects for each group. The analysis was done by multivariate analysis of etiologic concept. Result: In term birth, the most frequent physical activity intensities were: moderate intensity (64.6%, n = 82), light intensity (22%, n = 28), and vigorous intensity (13.4%, n = 17). In preterm birth, the most frequent physical activity intensities were: light intensity (40.1%, n = 51), vigorous intensity (33.9%, n = 43), and moderate intensity (26%, n = 33). Adjusted OR of preterm birth in light intensity versus moderate intensity was OR 5.32 (95% CI, 2.80-10.13;P = < 0.001). While adjusted OR of preterm birth in vigorous intensity compared with moderate intensity was OR 6.29 (95% CI, 3.28- 13.46;P = < 0.001). Work and sport have a significant association with preterm birth with OR 3.19 (95% CI, 1.62 - 6.28;P = 0.001) and OR 1.85 (95% CI,1.11 - 3.09; P= 0.017). Occupational conditions are also associated with preterm birth, including: weight lifting with OR 5.16 (95% CI, 1.10-24.08, P = 0.021), walking with OR 3.57 (95% CI, 1.61-7.92, P = 0.001), sitting with OR 2.79 (95% CI, 1.23-6.31, P = 0.011), and standing with OR 3.04 (95% CI, 1.40-6.59; P = 0.003). Conclusion: There is a significant relationship between the intensity of physical activity and type of physical activity in pregnant women with preterm birth. Keywords: intensity of physical activity, KPAS, physical activity, preterm labor Abstrak Tujuan: Mengetahui hubungan antara intensitas aktivitas fisik perempuan hamil dengan persalinan prematur dan mengetahui hubungan antara jenis aktivitas fisik perempuan hamil dengan persalinan prematur. Metode: Penelitian ini merupakan penelitian kasus kontrol yang dilakukan di RS Cipto Magunkusumo dan RS Karawang pada bulan Januari 2017 hingga Juni 2017 dengan kuesioner KPAS yang dikelompokkan menjadi dua, yaitu persalinan prematur dan persalinan cukup bulan. Jumlah sampel adalah 127 subjek untuk masing-masing kelompok. Analisis dilakukan dengan analisis multivariat konsep etiologik. Hasil: Pada persalinan cukup bulan, secara berurutan intensitas aktivitas fisik yang paling banyak dilakukan, antara lain : intensitas sedang (64.6%, n= 82), intensitas ringan (22 %, n = 28), dan intensitas berat (13.4 %, n = 17). Pada persalinan prematur, secara berurutan intensitas aktivitas fisik yang paling banyak dilakukan, antara lain : intensitas ringan (40.1 %, n = 51), intensitas berat (33.9 %, n = 43), dan intensitas sedang (26 %, n = 33). Hubungan antara intensitas aktivitas fisik ringan dibandingkan intensitas sedang untuk persalinan prematur memiliki OR 5.32 (IK 95% 2.80-10.13;P = < 0.001). Sedangkan hubungan antara intensitas aktivitas fisik berat dibandingkan intensitas sedang untuk persalinan prematur memiliki OR 6.29 (IK 95% 3.28- 13.46;p = < 0.001). Pekerjaan dan olahraga memiliki hubungan bermakna dengan persalinan prematur dengan OR 3.19 (IK 95% 1,62 – 6.28;p = 0.001) dan OR 1.85 (IK 95% 1.11 – 3.09;p= 0.017). Kondisi pekerjaan juga berhubungan dengan persalinan prematur, antara lain : angkat berat (OR 5.16; IK 95% 1.10-24.08; p = 0.021), berjalan (OR 3.57;IK 95% 1.61-7.92;p = 0.001), duduk (OR 2.79;IK 95% 1.23-6.31; p = 0.011 ), dan berdiri (OR 3.04 ;IK 95% 1.40-6.59;p = 0.003).